Development of cryopreservation techniques for preserving fungi - Mazlan, Tasnim (2017)
In recent years, tremendous increase in human population causes pressure on the forest and land resources. This condition in turn caused a decrease in the population of medicinal and aromatic plant species. Some animal species are also on the verge of extinction besides plants that are greatly threatened. For this matter, cryopreservation can be used as an effective means to conserve the germplasms of such species. Cryopreservation is a process in which living biological material is frozen and stored at low temperatures (-80⁰C). However, this low temperature is not a favourable condition for microbes and germplasms because this process will cause cell damage, protein denaturations and membrane injury towards the microbes. Therefore, a suitable cryoprotectant agent is needed in order to protect the microbes from being damage during the preservation process. Cryoprotectant agent acts like an antifreeze; they lower the freezing temperature and increase viscosity. Thus, the most effective cryoprotectant agent between glycerol, sucrose and honey will be studied and identified at the end of this research. Ten different species of fungi were used in this experiment for the preservation. One hundred microlitre of each fungus was cultured in Potato Dextrose Agar (PDA) media. Following after that, those fungi was tested and preserved by using different cryoprotectant agent with different percentage of concentration which are 10%, 15% and 20% of glycerol, sucrose and honey relatively. The survival of the fungi was observed after one month of preservation. Randomized Completely Block Design factorial (RCBD) was used in this experiment to evaluate the normal percentage and cost effective of cryoprotectant agent used. Glycerol is predicted to be the most effective cryoprotectant agent. ABSTRACT In recent years, tremendous increase in human population causes pressure on the forest and land resources. This condition in turn caused a decrease in the population of medicinal and aromatic plant species. Some animal species are also on the verge of extinction besides plants that are greatly threatened. For this matter, cryopreservation can be used as an effective means to conserve the germplasms of such species. Cryopreservation is a process in which living biological material is frozen and stored at low temperatures (-80⁰C). However, this low temperature is not a favourable condition for microbes and germplasms because this process will cause cell damage, protein denaturations and membrane injury towards the microbes. Therefore, a suitable cryoprotectant agent is needed in order to protect the microbes from being damage during the preservation process. Cryoprotectant agent acts like an antifreeze; they lower the freezing temperature and increase viscosity. Thus, the most effective cryoprotectant agent between glycerol, sucrose and honey will be studied and identified at the end of this research. Ten different species of fungi were used in this experiment for the preservation. One hundred microlitre of each fungus was cultured in Potato Dextrose Agar (PDA) media. Following after that, those fungi was tested and preserved by using different cryoprotectant agent with different percentage of concentration which are 10%, 15% and 20% of glycerol, sucrose and honey relatively. The survival of the fungi was observed after one month of preservation. Randomized Completely Block Design factorial (RCBD) was used in this experiment to evaluate the normal percentage and cost effective of cryoprotectant agent used. Glycerol is predicted to be the most effective cryoprotectant agent.